Multi-omics profiles refine L-dopa decarboxylase (DDC) as a reliable biomarker for prognosis and immune microenvironment of clear cell renal cell carcinoma - Chang, Kun; Su, Jiaqi; Li, Chuanyu; Anwaier, Aihetaimujiang; Liu, Wangrui; Xu, Wenhao; Qu, Yuanyuan; Zhang, Hailiang; Ye, Dingwei (Frontiers in Oncology, 2022)
Increasing evidence indicates that L-Dopa Decarboxylase (DDC), which mediates amino acids aberrant metabolism, is significantly associated with tumor progression. This study aimed to analyze DDC expression in tumor samples and its prognostic value for patients with clear cell renal cell carcinoma (ccRCC). We found significantly decreased DDC expression in ccRCC tissues compared with normal tissues from multiple independent cohorts based on multi-omics data. L-Dopa Decarboxylase expression levels of 532 patients with ccRCC (The Cancer Genome Atlas RNA-seq data), 226 ccRCC samples (Gene Expression Omnibus), and 101 ccRCC patients from E-MTAB-1980 cohort, and 232 patients with ccRCC with proteogenomic data (Fudan University Shanghai Cancer Center) were analyzed to investigate the prognostic implications of DDC expression. Cox regression analyses were implemented to explore the effect of DDC expression on the prognosis of pan-cancer. These findings revealed that lower DDC expression levels significantly correlated with shorter overall survival (P<0.001) of patients with ccRCC. These data indicate that DDC expression may serve as a prognostic biomarker for cancers. Moreover, we found that DDC expression significantly correlated with an immunosuppressive tumor microenvironment, higher intra-tumoral heterogeneity, elevated expression of immune checkpoint SIGLEC15, and possibly mediated malignant behaviors of ccRCC cells via the PI3k/Akt signaling pathway. In conclusion, the present study is the first to our knowledge to indicate that decreased L-Dopa Decarboxylase expression is significantly associated with poor survival and an immune-suppressive tumor microenvironment in ccRCC. These findings suggest that L-Dopa Decarboxylase can serve as a biomarker for guiding molecular diagnosis and facilitating the development of novel individual therapeutic strategies for patients with advanced ccRCC.